PENGARUH PENERAPAN TOKEN ECONOMY TERHADAP KEDISIPLINAN ANAK USIA 4-5 TAHUN DI KELOMPOK BERMAIN KEMBANG SEKUNTUM KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - YUTRI, DEPI; ', Wilson; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the author's observation, planting discipline in Kembang Sekuntum Playgroup Village keresek not maximized seen when the learning process. So the application needs to be given token economy. This study aims to determine the effect of applying token economy to discipline children aged 4-5 years in group play Kembang Sekuntum District of Gunung Toar. Samples in this study is 14 students. The data collection techniques used are observasi.Teknik data were analyzed using t-test using SPSS 17.0. The study hypothesis is there is positive and significant correlation between the application token economy to discipline children aged 4-5 years. It can be seen from the analysis of data obtained with Asymp Z -3.333. Sig. (2-tailed) of 0.001 or less than 0.05 it was determined that there are differences in the level of discipline of children before and after treatment using a token economy. Then Ho is rejected and Ha accepted that it can be concluded that there is a significant effect in the application of engineering token economy to discipline children aged 4-5 years. The magnitude of the effect of the application of engineering token economy to discipline the behavior of children aged 4-5 years can be seen through the acquisition of N-Gain score with a percentage of 74%.